Labirinto de gênero e ambiente : diálogos com alguns jovens quilombolas da comunidade de Mata Cavalo - Santos, Elizete Gonçalves dos (2015)
Quilombo communities in Brazil are struggling today for the recognition of their lands, cultures and access to basic rights for the permanence of their people and knowledge. With the apparatus of public policy - laws, programs and decrees - the situation of these communities has improved, but the struggle continues. Our research aims to understand the perception of gender and young subjects environment high school students of the State School Professor Teresa Conceição de Arruda, located in Rural Black Community Forest of Mata Cavalo, in the municipality of Nossa Senhora do Livramento, Mato Grosso. Along the way, we used as a method the qualitative approach of the case study, due to the interest in deepening the specifics of gender and environmental perceptions by the group chosen. Eleven interviews with students both female and male were conducted. Besides the interviews, there was a thematic workshop with dolls of some ethnic groups (White, Black, Yellow), with the objective of collecting stories, interpretations of the surveyed young people about socio-environmental relationships. Community women have a long history of struggles for the final possession of the land, the right to live their culture, and for building their identity. However, the young participants of the survey have shown little involvement with the historical struggle of the community. They know they express and the history of conflicts, through stories told by older community. The environment of locality was described by the young people as the place of origin of their families, space in which they can build their identities linked to African origin. In relation to gender relations in the community, young people report differentiated and fixed roles for men and women. Remain many stereotypes about women, as they belong to the household. To the male, there is an entirely public space. Such division causes paradoxical situations within the community, since, as already mentioned in other studies, women took the lead of public struggles against the expropriation of their lands. We hope this research can contribute to increase the visibility of such a group and bring reflections that arouse the commitment to the struggle of the Mata Cavalo youth.